METHODOLOGY FOR SYNCHRONIZING THE PERFORMANCE OF GROUP EXERCISES IN RHYTHMIC GYMNASTICS (SCIENCE TIME JOURNAL, 2026)
This article examines the methodology for synchronizing the performance of group exercises in rhythmic gymnastics. The study focuses on the theoretical and practical foundations of achieving coordination, rhythmic unity, and technical consistency among athletes during group routines. Particular attention is paid to training methods aimed at developing temporal accuracy, spatial orientation, motor coordination, and collective interaction. The research analyzes modern pedagogical approaches, including the use of music-based training, visual and auditory cues, and phased rehearsal techniques to enhance synchronization. The results of the study demonstrate that the systematic application of specialized synchronization methodologies contributes to improved performance quality, artistic expression, and competitive effectiveness in group rhythmic gymnastics routines.